The Opposite - MacRae, Tom (Peachtree, 2006)
Nate wakes up one morning to find The Opposite standing on his bedroom ceiling, and it causes him trouble at home and at school, changing what Nate wants to do into its opposite, until Nate finds a way to outwit it.